ROMANTIC RELATIONSHIP METAPHORS OF UNIVERSITY STUDENTS: IS LOVE A TERRACE OF THE HOUSE WITH A SEAVIEW? - Evrim ÇETİNKAYA YILDIZ; Sümeyye DERİN; Almila Elif SELÇUKLU (International Journal of Eurasia Social Sciences, 2018)
This study aimed to find out university students’ metaphoric perceptions toward “romantic relationships”. With this purpose in mind, 508 volunteered undergraduate students (57% female, 43% male; ages range 19-22) from Erciyes University, Turkey participated in the study. To find out the participants’ metaphoric explanation of romantic relationship, students were asked to fill in the blanks in a compound sentence; “Romantic relationship is … Because ... .” Descriptive analysis and qualitative analysis were used to analyze the data. First, participants’ metaphors about romantic relationship were categorized according to the meaning of each metaphor and an inclusive category name was constituted. In this process, literature on romantic relationship metaphors was considered. Later, 3 other researchers categorized the data using the same category list. Thus, interrater reliability coefficient was calculated and was found 0.86. Fifteen main themes emerged according to participants metaphoric expressions. The themes that had high percentiles were “source of happiness”, “unsettled” and “togetherness”. And the themes that had low percentiles were “innocent”, “irresistible”, “instructive”, and “journey”. Results were discussed under the light of related literature with quotations and cultural perspective. Finally, suggestions for researchers who are interested in romantic relationships and recommendations for counselors were presented.